2006
DOI: 10.1038/sj.bjc.6603301
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter phase III trial comparing irinotecan-gemcitabine (IG) with gemcitabine (G) monotherapy as first-line treatment in patients with locally advanced or metastatic pancreatic cancer

Abstract: Our purpose was to determine the response rate and median and overall survival of gemcitabine as monotherapy versus gemcitabine plus irinotecan in advanced or metastatic pancreatic cancer. Patients with histologically or cytologically confirmed adenocarcinoma who were chemotherapy and radiotherapy naive were enrolled. Patients were centrally randomised at a one-to-one ratio to receive either gemcitabine monotherapy (900 mg m À2 on days 1, 8 and 15 every 4 weeks (arm G), or gemcitabine (days 1 and 8) plus irino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(70 citation statements)
references
References 25 publications
1
67
0
2
Order By: Relevance
“…Table 3 summarizes 13 randomized phase III trials that attempted to improve upon the survival outcomes achieved with gemcitabine alone, typically by adding a second cytotoxic agent [20,[31][32][33][34][35][36][37][38][39][40][41][42]. With the exception of the gemcitabine plus capecitabine experimental arm reported by Cunningham et al [35] in abstract form only as of this review, these efforts have failed to identify a gemcitabine-based chemotherapy doublet that has produced significantly better median or 1-year survival outcomes.…”
Section: Phase III Combination Chemotherapy Trialsmentioning
confidence: 99%
“…Table 3 summarizes 13 randomized phase III trials that attempted to improve upon the survival outcomes achieved with gemcitabine alone, typically by adding a second cytotoxic agent [20,[31][32][33][34][35][36][37][38][39][40][41][42]. With the exception of the gemcitabine plus capecitabine experimental arm reported by Cunningham et al [35] in abstract form only as of this review, these efforts have failed to identify a gemcitabine-based chemotherapy doublet that has produced significantly better median or 1-year survival outcomes.…”
Section: Phase III Combination Chemotherapy Trialsmentioning
confidence: 99%
“…In fact, not only PMX, as above reported, has demonstrated to be active as single agent but CPT-11 also has demonstrated activity, although modest, in pancreatic cancer (Wagener et al, 1995;Klapdor and Fenner, 2000;Pizzolato and Saltz, 2003). Unfortunately, a recently reported phase III trial of GEM with or without CPT-11 revealed no survival benefit (Rocha Lima et al, 2004;Stathopoulos et al, 2006) but other combinations of CPT-11 should continue to be explored in an effort to further improve the treatment of this chemorefractory disease (Taieb et al, 2006). Secondly, each drug in this combination has an independent mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Many phase II trials have demonstrated the efficacy of gemcitabine-based combinations, which comprise other cytotoxic molecules such as capecitabine, 5-FU, cisplatin, irinotecan [34][35][36][37] or the targeted agents sorafenib and cetuximab [38][39][40] . However, in some randomized phase III trials of gemcitabine based chemotherapy combinations, these combinations failed to show statistically significant improvement in patient's overall survival when compared to gemcitabine used as a single-agent [41][42][43][44][45][46] . Nowadays, gemcitabine is used in combination with taxol, a paclitaxel albumin-stabilized nanoparticle formulation (nab-paclitaxel) that is commercially known as abraxane.…”
Section: Chemotherapy Gemzar -Gemcitabinementioning
confidence: 99%